KRITIK INTRINSIKALITAS DAN EKSTRINSIKALITAS SASTRA MODERN DALAM KAJIAN SASTRA ARAB MODERN - Abd Aziz; M. Imam Sofyan Yahya (Institut PTIQ Jakarta, 2019)
In the practice of literary criticism, including Arabic literature, there are two approaches in evaluating literary works, namely the intrinsic approach and the extrinsic approach. The intrinsic approach bases itself on the objective value of literary works itself without connecting with other sciences, or approaches that seek to see literary works objectively with the propositions of linguistics and literary aesthetics. From this approach was born a flow of semiotic literary criticism and structural literary criticism. Meanwhile, the extrinsic approach uses certain scientific measures in evaluating literary works. The extrinsic approach to literary criticism seeks to see literary works from the viewpoint of disciplines outside of literature. This approach gave birth to sociological literary criticism, psychological literary criticism, archaeological literary criticism, moral literary criticism, philosophical literary criticism, and others.